THE INFLUENCE OF GALLERY WALK MODEL TOWARDS STUDENTS’ SPEAKING SKILL - ELIS ANDINI; SUNARA SUNARA; SUMPENA ROHAENDI (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2019)
The purpose of the researchwas to investigate whether or not the influence gallery walk model towards students speaking skill. The resarch was onducted in SMPN 2 Purwadadi. This research use Quantitative method and used non-equivalent control group design categorized as Quasi expeimental design. Two classes were selected from seventh as experiment and control class. The result of the data analysis were as follows. Mean score of pretest in experiment class was 15.66 and standard deviation was 2.057. while, mean score in control class was 16.25 and standard deviaton was 1.586 . further, mean score of posttest in experiment class was 17.81 and standard deviation was 1.533. while, mean score posttest in control class was 17.66 and standard deviation was 1.619. The result of T-test shows that value sig. (2–tailed) was 201in pretest. It was higher than 0.05. Then, there was not diffence of mean between experiment and control class in pretest. The value sig. (2–tailed) was 6.93 in posttest. It was higher than 0.05. Then, there was not difference of means between experiment and control class in posttest. Based on the result of model summary in simple regression, R squere was 0.051 with significance 0.214. it means that the influence of independent variable (questionnaire) towards dependent variable (posstest) was 0.05 %. While, 99.95 % influenced by other variable. Then model of regressing was not good enough as predictors. Based on the coefficient, constant of 20.308 if there was nothing questionnaire, then value of posttest is -0.046. Regression coefficien X of (-0.214) it means each addition 1 value of questionnaire then decline of posttest value of (-0.214). it shows that there was not the significance influence of Gallery walk model toward students speaking skill.